To study the effect of grinding parameters on surface roughness and material removal rate of cylindrical grinding of heat treated en 47 steel (Journal of Mechanical Engineering, 2016)
This research paper attempts to optimize the effect of input parameters to minimize surface roughness and maximize the material removal rate in cylindrically grinding of EN 47 steel material. Taguchi L18 (2)¹, (3)5 orthogonal array or mixed level of parameters have been applied to experimental design with the help of mini tab software. The result reveals that grain size and work speed are the most significant factors to influence material removal rate and surface roughness. The optimum set of input parameters for maximizing the material removal rate and optimum surface roughness have also been found